Bangladesh Development Update, April 2015 - World Bank (Dhaka, 2015)
This report highlights recent economic updates in Bangladesh as of April 2015. Economic growth in Bangladesh was gaining momentum in the first half of FY15. Capacity utilization improved and investments were showing some signs of recovery. This growth was also job-friendly. The 12-monthly-moving average inflation decelerated from 7.6 percent in February 2014 to 6.8 percent in February 2015. The resilience of the Bangladesh economy continues to be tested by faltering political stability, weak global markets, and structural constraints. These are inhibiting the economy s income growth as well as progress on shared prosperity. Despite the emergence of a $1.3 billion deficit in the current account in the first seven months of FY15, the surplus in the overall balance of payments has been sustained, leading to continued accumulation of official foreign exchange reserves to prevent nominal exchange rate appreciation. Reserves are at a comfortable level at over 6 months of imports of goods and services. Fiscal policy has remained consistent with macroeconomic stability. Tax revenue growth has been weaker than targeted while expenditure have also been short due as usual to an implementation shortfall. The projected recovery in global growth, particularly in the United States and the Euro Zone, and continued softness in international commodity prices, bode well for Bangladesh. The country will need to restore political stability and implement faster structural reforms to capitalize on these opportunities. The potential GDP growth rate is on a declining path due to declining labor force growth and stagnant productivity growth, as well as the rate of capital accumulation. Raising the low Female Labor Force Participation (FLFP) rate offers on opportunity to boost the economy s potential growth rate. Moving forward, the biggest challenge remains ensuring durable political stability. This is a precondition for accelerated, inclusive, and sustainable growth.